Abiotic stress-mediated modulation of the chromatin landscape in Arabidopsis thaliana. (11th June 2020) - Raxwal, Vivek Kumar; Ghosh, Sourav; Singh, Somya; Katiyar-Agarwal, Surekha; Goel, Shailendra; Jagannath, Arun; Kumar, Amar; Scaria, Vinod; Agarwal, Manu
Abstract : We illustrate how different abiotic stresses not only reshape the chromatin architecture of the Arabidopsis genome but also rewire the transcription factor network to fine-tune gene expression. Abstract: Limited information is available on abiotic stress-mediated alterations of chromatin conformation influencing gene expression in plants. In order to characterize the effect of abiotic stresses on changes in chromatin conformation, we employed FAIRE-seq (formaldehyde-assisted isolation of regulatory element sequencing) and DNase-seq to isolate accessible regions of chromatin from Arabidopsis thaliana seedlings exposed to either heat, cold, salt, or drought stress. Approximately 25% of regions in the Arabidopsis genome were captured as open chromatin, the majority of which included promoters and exons. A large proportion of chromatin regions apparently did not change their conformation in response to any of the four stresses. Digital footprints present within these regions had differential enrichment of motifs for binding of 43 different transcription factors. Further, in contrast to drought and salt stress, both high and low temperature treatments resulted in increased accessibility of the chromatin. Also, pseudogenes attained increased chromatin accessibility in response to cold and drought stresses. The highly accessible and inaccessible chromatin regions of seedlings exposed to drought stress correlated with the Ser/Thr protein kinases (MLK1 and MLK2)-mediated reduction and increase in H3 phosphorylation (H3T3Ph), respectively. The presented results provide a deeper understanding of abiotic stress-mediated chromatin modulation in plants.